2021
DOI: 10.1089/thy.2020.0720
|View full text |Cite
|
Sign up to set email alerts
|

Evidence-Based Use of Levothyroxine/Liothyronine Combinations in Treating Hypothyroidism: A Consensus Document

Abstract: Background: Fourteen clinical trials have not shown a consistent benefit of combination therapy with levothyroxine (LT4) and liothyronine (LT3). Despite the publication of these trials, combination therapy is widely used and patients reporting benefit continue to generate patient and physician interest in this area. Recent scientific developments may provide insight into this inconsistency and guide future studies. Methods: The American Thyroid Association (ATA), British Thyroid Association (BTA), and European… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
71
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(77 citation statements)
references
References 112 publications
0
71
0
6
Order By: Relevance
“…In patients with TRa mutations, low T4/T3 ratio is typical and symptoms of hypothyroidism with variable manifestations are seen. The consensus report on evidence-based use of L-T3/L-T4 combinations in treating hypothyroidism reported that there is dissatisfaction with the existing standard of care and that "a new well-designed adequately powered clinical trial of combination therapy" is needed because not all studies met the current standard requirements (130).…”
Section: Use Of L-t4 and L-t3mentioning
confidence: 99%
“…In patients with TRa mutations, low T4/T3 ratio is typical and symptoms of hypothyroidism with variable manifestations are seen. The consensus report on evidence-based use of L-T3/L-T4 combinations in treating hypothyroidism reported that there is dissatisfaction with the existing standard of care and that "a new well-designed adequately powered clinical trial of combination therapy" is needed because not all studies met the current standard requirements (130).…”
Section: Use Of L-t4 and L-t3mentioning
confidence: 99%
“…We can adequately correct biochemical euthyroidism in total thyroidectomized patients with levothyroxine (LT4) replacement therapy, but some of them still complain of disturbances in their psychological and physical well-being (1). The reason for this may be the absence of some T3 in their circulation (2). Our thyroid synthesizes 2 different thyroid hormones (TH): one of them is thyroxine (T4) which has 4 iodine atoms; the second one is its biologically active brother 105 with 3 iodine atoms called triiodothyronine (T3).…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, those with low baseline serum total T3 levels while taking LT4 monotherapy should also be include. Noteworthy, they suggest that future combination therapy trials should consider including polymorphism genotyping, and should be adequately powered to study the effect of this polymorphism on trial outcomes (6). The recommended initial dose of LT4:LT3 is 13:1 to 20:1, a ratio that mimics the ratio of physiological thyroxine (T4) and T3 secretion by the human thyroid gland, representing a dose of 5 or 10 μg LT3 for patients taking 100 to 200 μg LT4.…”
mentioning
confidence: 99%
“…The recommended initial dose of LT4:LT3 is 13:1 to 20:1, a ratio that mimics the ratio of physiological thyroxine (T4) and T3 secretion by the human thyroid gland, representing a dose of 5 or 10 μg LT3 for patients taking 100 to 200 μg LT4. If no improvement is seen after 3-6 months of treatment, assessed by questionnaires such as ThyPRO, treatment should be discontinued (6).…”
mentioning
confidence: 99%